Angiogenic Factors and Renal Disease in Pregnancy. (28th July 2011) - Rhee, Julie S.; Young, Brett C.; Rana, Sarosh
Abstract : Background . Preeclampsia is difficult to diagnose in patients with underlying renal disease and proteinuria. Prior studies show that there is an angiogenic factor imbalance with elevated levels of antiangiogenic proteins soluble fms-like tyrosine kinase 1 (sFlt1) and soluble endoglin (sEng) and reduced levels of the proangiogenic protein, placental growth factor (PlGF) in women with preeclampsia. These angiogenic biomarkers may be useful in distinguishing preeclampsia from other conditions of pregnancy, which may present with overlapping clinical characteristics. Cases . Case 1: A multiparous woman at 18 weeks gestation with nephrotic syndrome presented with hypertensive emergency and worsening renal insufficiency. She underwent induction of labor for severe preeclampsia. Her sFlt1 and sEng levels were at the 97 percentile while her PlGF level was undetectable (less than the 1st percentile). Case 2: A nulliparous woman with lupus nephritis at 22 weeks gestation presented with fetal demise and heart failure. Three weeks previously, the patient had developed thrombocytopenia and hypertensive urgency. She underwent dilation and evacuation. Her angiogenic profile was consistent with severe preeclampsia. Conclusion . Angiogenic factors may provide evidence to support a diagnosis of preeclampsia in patients with preexisting renal disease and proteinuria, conditions in which the classical definition of hypertension and proteinuria cannot be used.